Delphine Jones Takes a Chance - Morrey, Beth (New York : G. P. Putnam's Sons, 2022)
"A heartening and life-affirming novel about a single mother learning to make a bigger life, and the power of human connection to grow our worlds"--.
new book 2022 spring.
Keywords: Domestic fiction; Novels